DESAIN METODE KOLABORATIF MAHFUDZAT KONTEKSTUAL UNTUK PENGUATAN KARAKTER SISWA PADA MATERI SIFAT MUKMIN YANG SEMPURNA - Maryam Pakaya; Elma Toino; Wardiansyah Putra A Sanu; Kiki Rizki Wulandari (STIT Darul Hijrah Martapura, 2026)
Mahfudzat learning plays an important role in shaping students' character in Islamic educational institutions. However, the implementation is still dominated by a memorization approach, so students are unable to internalize the values of Mahfudzat optimally. This research aims to develop the design of the Mahfudzat Collaborative Character Learning (MCCL) and identify its advantages and limitations. This research uses a Research and Development (R&D) approach based on the ADDIE model, limited to the Analysis and Design stages. Data were collected through observation, documentation studies, and literature reviews, then analyzed in a qualitative descriptive manner. The results of the study show that Mahfudzat learning remains dominated by memorization, with varying levels of understanding among students. Based on the results of the needs analysis, an MCCL conceptual design was developed that integrates Mahfudzat learning, a collaborative approach, and character strengthening grounded in hadith values across five stages of learning. This design is intended to encourage active student participation, facilitate the internalization of Islamic values, and strengthen character education through collaborative, reflective, and contextual learning. Further research is needed to test the effectiveness of MCCL at the Development, Implementation, and Evaluation stages.